Sliding fragility of block type non structural components. Part 1 Unrestrained components. - Garcia, D. Lopez
Motivated by the development of performance based design guidelines with emphasis on both structural and non structural systems, this paper focuses on seismic vulnerability assessment of block type unrestrained non structural components under sliding response on the basis of seismic inputs specified by current seismic codes. Two sliding related failure modes are considered : excessive relative displacement and excessive absolute acceleration. It is shown that an upper bound for the absolute acceleration response can be assessed deterministically, for which a simple yet completely general equation is proposed. In contrast, fragility curves are proposed as an appropriate tool to evaluate the excessive relative displacement failure mode. Sample fragility curves developed through Monte Carlo simulations show that fragility estimates obtained without taking into account vertical base accelerations can be significantly unconservative, especially for relatively large values of the coefficient of friction. It is also found that reasonable estimates of relative displacement response at stories other than the ground in multistorey buildings cannot in general be obtained by simply scaling the ground acceleration to the peak acceleration at the corresponding storey. Failure modes considered in this study are found to be essentially independent of each other, a property that greatly simplifies assessment of conditional limit states.
Keywords: Seismic fragility; Non structural components; Rigid blocks; Sliding response